What Are The Differences In Melasma Diagnosis And Management Across Diverse Ethnic Populations With Varying Skin Types? : A Systematic Review - Juliave Dora Odheta Purba; Ketut Kwartantaya Winaya; Pande Agung Mahariski (International Medical Journal Corp. Ltd, 2025)
Introduction: Melasma presents significant therapeutic challenges due to its varied presentation across diverse ethnic populations and skin types. There is a critical need for treatment strategies tailored to a patient's ethnic background and Fitzpatrick skin type to optimize efficacy while minimizing risks such as post-inflammatory hyperpigmentation (PIH), particularly in darker skin tones (Fitzpatrick III-V). Methods: This systematic review was conducted following PRISMA guidelines. A comprehensive search of PubMed, Semantic Scholar, Springer, and Sagepub databases was performed using a PICO-based strategy to identify studies on melasma diagnosis and management with respect to ethnic variations or skin types. Thirty studies met the inclusion criteria for final analysis. Results: The Melasma Area and Severity Index (MASI) was the most common diagnostic tool. Treatment efficacy varied significantly by population. In Indian cohorts, salicylic-mandelic acid peels and topical tranexamic acid were found to be safe and effective. Asian populations showed a preference for combination laser therapies, such as dual toning and picosecond lasers, to reduce the risk of rebound hyperpigmentation. Triple combination creams were effective in Middle Eastern skin , and non-hydroquinone alternatives demonstrated efficacy across multi-ethnic groups. High recurrence rates and PIH remain major challenges, especially in darker skin. Conclusion: The evidence confirms that a 'one-size-fits-all' approach to melasma is obsolete. Effective management requires a personalized strategy that considers the patient's ethnicity and skin phototype to balance efficacy with pigmentary safety. Combination therapies targeting multiple pathogenic pathways are superior , and the use of versatile agents like tranexamic acid alongside strict sun protection is crucial. Individualizing treatment is paramount for achieving sustained improvement and managing this chronic condition.